Environmental impact statements : a practical guide for agencies, citizens, and consultants - Kreske, Diori L. (New York : John Wiley and Sons, 1996)
Basic concepts in Environmental Impact Statements (EIS); Laws and procedures; Planning & process; Environmental impact in U.S. & other nations; Project management; Public involvement; writing an EIS.
Keywords: Environment; Environmental impact statements; Environmental impact statements -- United States